Transcriptome analysis approaches for the isolation of trichome-specific genes from the medicinal plant Cistus creticus subsp. creticus - Falara, Vasiliki; Fotopoulos, Vasileios; Margaritis, Thanasis; Anastasaki, Thalia; Pateraki, Irene; Bozabalidis, Artemios M.; Kafetzopoulos, Dimitris; Demetzos, Costas; Pichersky, Eran; Kanellis, Angelos K. (My University, 2008)
Cistus creticus subsp. creticus is a plant of intrinsic scientific interest due to the distinctive pharmaceutical properties of its resin. Labdane-type diterpenes, the main constituents of the resin, exhibit considerable antibacterial and cytotoxic activities. In this study chemical analysis of isolated trichomes from different developmental stages revealed that young leaves of 1–2 cm length displayed the highest content of labdane-type diterpenes (80 mg/g fresh weight) whereas trichomes from older leaves (2–3 or 3–4 cm) exhibited gradual decreased concentrations. A cDNA library was constructed enriched in transcripts from trichomes isolated from young leaves, which are characterized by high levels of labdane-type diterpenes. Functional annotation of 2,022 expressed sequence tags (ESTs) from the trichome cDNA library based on homology to A. thaliana genes suggested that 8% of the putative identified sequences were secondary metabolism-related and involved primarily in flavonoid and terpenoid biosynthesis. A significant proportion of the ESTs (38%) displayed no significant similarity to any other DNA deposited in databases, indicating a yet unknown function. Custom DNA microarrays constructed with 1,248 individual clones from the cDNA library facilitated transcriptome comparisons between trichomes and trichome-free tissues. In addition, gene expression studies in various Cistus tissues and organs for one of the genes highlighted as the most differentially expressed by the microarray experiments revealed a putative sesquiterpene synthase with a trichome-specific expression pattern. Full length cDNA isolation and heterologous expression in E. coli followed by biochemical analysis, led to the characterization of the produced protein as germacrene B synthase.
Keywords: Cistus creticus subsp. creticus; DNA microarrays; EST analysis; Gene expression; Germacrene B synthase; Trichomes